Role of Teacher’S In Career Development of the Secondary School Student: Exploring the Challenges and Opportunities for Secondary School Teachers (Journal of Advances and Scholarly Researches in Allied Education, 2016)
The teachers are an important constituent in theinstructional process that can play a crucial role in shaping the personalityof the students. The students of this era  were facing complexity to achieve the goal 100% in all the directions.The students of secondary school are in the adolescence. Adolescence is themost important part of the human life. The child experiences a number ofchanges in this transitional   period oflife. They also feel unsecured themselves. Due to the change in the   childhood to adulthood the students undergowith emotional, psychological, social and many other changes. That’s why astudent feels an extra pressure to achieve  the success in life. In the present time the aim of education is toachieve the fullest possible realization of possibilities inherent in theindividual. The education   fosters allaspects of all individuals’ personality. The student’s life is getting complexday by day. Students in the twenty-first century have facing many   complex and difficult situations  i.e. to make wise curricular and othercurricular  choices, to acquire basicstudy  skills for optimumachievement,   adjustment   with  peers etc. That is the reason that there is a challenge for a teacher todevelop   overall personality of astudent of the secondary school.